WAYS OF INDIVIDUALIZATION OF EDUCATION FOR CHILDREN WITH AUTISM SPECTRUM DISORDERS: THE EXPERIENCE OF SPECIAL PEDAGOGUES' - Kaffemaniene, Irena; Kulese, Zivile (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Researchers shows that both in Lithuania and in other countries the education of students with autism spectrum disorders (ASD) still poses significant challenges, especially for teachers in general education schools. Thus, not only students with ASD but also their teachers need the support of special needs teachers in the educational process. However, there is a lack of research in Lithuania on the strategies used by special needs teachers to educate students with special educational needs (SEN). The research aim - to examine special pedagogues’ experience in individualizing the education of students with ASD. A theoretical analysis of the educational strategies and ways of individualized education of students with ASD has been performed. Empirical research was carried out by the method of survey of special pedagogues who have experience in educating these children. Quantitative data analysis was performed using the methods of descriptive statistics. According to the special pedagogues, the factors of individualization of education of students with ASD are the peculiarities of their learning, communication and cognitive skills of those children. The analysis of the educational goals indicated by respondents revealed their orientation towards the individualization of education, support for students participation in the educational process, etc.